The consumption of fast food and obesity associated with hypertension among restaurant workers in Jordan - Shayma Taha; Madi Al-Jaghbir; Mahmoud Abughoush; Amal Aljanada (Clinical Nutrition Open Science)
Summary: Background: Fast food consumption among those who work in restaurants is a regular occurrence. Frequent consumption of high-caloric foods is a leading cause of obesity which is also a modifiable factor of risk for hypertension. Studies predict that the prevalence of hypertension would rise by 7.2% by 2030 compared to 2013 projections, demonstrating the urgent need for treatments to address the etiology of hypertension. Objective: This study's primary objective is to investigate how fast-food intake, portion size, obesity, and hypertension are related among Amman, Jordan, restaurant workers. Methods: A descriptive quantitative cross-sectional design was applied to investigate whether or not there is an association between obesity, regular intake of fast food, and high blood pressure among employees in the food services industry. A convenience sample of 386 restaurant employees was recruited from various restaurants in Amman, Jordan. A self-administered questionnaire that asked about food products, frequency of consumption, and the portion size was used to gather the data. An electric blood pressure monitor was used to track the sample's blood pressure while anthropometric measurements were obtained to determine height and weight. Chi-square test and Spearman rank-ordered correlation approach were used for the study. Results: The analysis tests indicate that there is a significant positive correlation between the frequency of fast-food consumption and hypertension (rbp = 0.513, P <0.001). The second correlation test analysis indicates that there is a significant positive correlation between the portion size of fast food and body mass index (rs = 0.529, P <0.001). Moreover, there's a significant positive correlation between the age groups and hypertension (X2=27.686, P<0.001), a significant positive association between obesity and the males of the participants (X2=33.134, P<0.001), and a significant positive association between obesity and age groups (X2=32.132, P<0.001). Conclusions: The significant association between fast food, obesity, and hypertension among restaurant workers points out that fast food consumption is related to high rates of developing obesity and hypertension among restaurant workers. Data should be used by both health experts and management in the development of workplace health interventions that put an emphasis on restaurant employees.